NAVIGATING CULTURAL AWARENESS IN GENERATIVE AI-ASSISTED ENGLISH LANGUAGE TEACHING: INDONESIAN EFL TEACHERS' PERSPECTIVES - Aksendro Maximilian; Mohammed Hejash; Purnama Hanan Murod (JETA (Journal of English Teaching and Applied Linguistic), 2026)
This study investigates Indonesian EFL teachers' perceptions of cultural awareness in GenAI-assisted English language teaching and explores the opportunities and challenges they perceive when addressing cultural awareness through AI-generated instructional materials. A quantitative survey design was employed involving 60 Indonesian junior high school EFL teachers who had prior experience using Generative AI applications for instructional purposes. Data were collected through a structured questionnaire and analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings indicate that teachers hold highly positive perceptions toward the importance of integrating cultural awareness into AI-assisted English language teaching. Participants emphasized that AI-generated cultural content should be critically evaluated before classroom implementation and that English instruction should integrate both Indonesian and global cultural perspectives. Teachers also perceived Generative AI as a valuable resource for creating culturally diverse instructional materials and enriching classroom learning. However, concerns were raised regarding cultural bias, inaccurate cultural information, limited representation of Indonesian local cultures, and students' overreliance on AI-generated content. The study concludes that the effective integration of GenAI into English language teaching depends not only on technological capability but also on teachers' intercultural competence, critical AI literacy, and pedagogical judgment.